Genetic diversity and phylogenetic relationships of Nigerian indigenous pigs in Southwestern Environment of Nigeria using microsatellite loci - Oluwole, Olufunke; Okoth , Edward; Adeola , Adeniyi Charles; Ogugo, Moses (Nigerian Journal of Animal Science, 2023)
Indigenous pigs in Nigeria are hardy and resistant to local harsh environmental conditions. This study investigated the genetic diversity and phylogeny of Nigerian indigenous pig (NIP) from three locations in Southwestern Nigeria including Ilaramokin (n = 13), Igangan (n = 5), and Igbara-Odo (n = 7) using eight microsatellite markers. The overall mean of number of alleles (Na) was 2.63±0.27 with effective number of allele (Ne) mean of 1.94±0.17. The SW 122 marker had the highest Na of 4.67±0.67 with Ne of 3.24±0.67; 0.70±0.05 and 0.67±0.06 for Ho (observed heterozygosity) and He (Expected Heterozygosity) respectively. The mean estimate 2.30±0.60 of Nm (gene flow) showed low gene flow between the three populations. The overall mean of F statistics parameters of genetic differentiation estimated were 0.06±0.07, 0.11±0.60 and 0.17±0.06 for FIS (within population inbreeding estimate,), FST (estimate of population differentiation) and FIT (overall global heterozygote deficit across population) respectively. The principal coordinate plot showed separate clustering of the three NIP populations. The phylogenetic tree showed common ancestry and separation due to geographic locations for the three NIP populations. Genetic distance showed closer relationship between the Ilaramokin and Igbara-Odo NIPs. These results will be useful in genetic improvement of the remaining pure NIP populations.